2020
DOI: 10.1007/s12274-020-3152-7
|View full text |Cite
|
Sign up to set email alerts
|

Mechanosynthesis of polymer-stabilized lead bromide perovskites: insight into the formation and phase conversion of nanoparticles

Abstract: The application of polymers to replace oleylamine (OLA) and oleic acid (OA) as ligands for perovskite nanocrystals is an effective strategy to improve their stability and durability especially for the solution-based processing. Herein, we report a mechanosynthesis of lead bromide perovskite nanoparticles (NPs) stabilized by partially hydrolyzed poly(methyl methacrylate) (h-PMMA) and high-molecular-weight highly-branched poly(ethylenimine) (PEI-25K). The as-synthesized NP solutions exhibited green emission cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Additionally, the CsPbBr 3 MC solution, which was not synthesized with PAA, was degraded by ethanol and water. Generally, the chemical structure of the ligands affects the optical properties and film morphology of the perovskite NCs [40][41][42][43]. Sichert et al reported that the nanoplatelet thickness could be controlled by the amount of OAm, which could affect the quantum size effect in two-dimensional perovskite [40].…”
Section: Absorption and Emission Spectroscopymentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the CsPbBr 3 MC solution, which was not synthesized with PAA, was degraded by ethanol and water. Generally, the chemical structure of the ligands affects the optical properties and film morphology of the perovskite NCs [40][41][42][43]. Sichert et al reported that the nanoplatelet thickness could be controlled by the amount of OAm, which could affect the quantum size effect in two-dimensional perovskite [40].…”
Section: Absorption and Emission Spectroscopymentioning
confidence: 99%
“…Sichert et al reported that the nanoplatelet thickness could be controlled by the amount of OAm, which could affect the quantum size effect in two-dimensional perovskite [40]. Jiang et al reported various optical properties depending on the amount of polymer, which improved the stability by forming a shell on the perovskite surface [42]. It has also been reported that the optical properties of perovskite can be significantly decreased by side reactions when polymers or monomolecular ligands are used in excess amounts [42,43].…”
Section: Absorption and Emission Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] Polymethyl methacrylate (PMMA) has been widely explored as a host polymer because of its excellent optical properties, air resistance, and easy processing, [10][11][12] which promoted the development of PNC-PMMA composites for application in liquid crystal display (LCD) backlights, micro-LED displays, and light communication. [13][14][15][16][17][18] Despite enormous progress made in synthesis methods and device fabrication, PNCs-PMMA still show unsatisfactory efficiency and stability that have become the major obstacles to their practical applications. The ionic surface and dynamic ligand binding induce fast degradation and fluorescence quenching of the PNCs upon exposure to polar solvents, humidity, oxygen, and light.…”
Section: Introductionmentioning
confidence: 99%
“…Metal halide perovskites are promising for next-generation display and lighting applications due to their high photoluminescence quantum yield (PLQY), tunable emission wavelength and low cost, and excellent optoelectronic performance. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Only five years after the first demonstration of room-temperature electroluminescence (EL) from perovskite light-emitting diodes (PeLEDs), lead-based PeLEDs have already achieved an impressive set of achievements, 17 with the highest external quantum efficiency (EQE) of both green and red light-emitting perovskite diodes exceeding 24% to date. 18,19 However, the development of blue LEDs as a key optoelectronic component is lagging far behind that of green and red LEDs.…”
Section: Introductionmentioning
confidence: 99%